Changes in female sexual function during the retirement transition - Virkkunen, Viivi; Kero, Katja; Stenholm, Sari; Polo-Kantola, Päivi (Lippincott, 2026)
Objectives:
For many women, retirement represents a significant transition in late adulthood, which may result in many alterations in lifestyle habits and behavioral patterns. Several factors known to improve during the retirement transition are also associated with female sexual function; however, the literature on the influence of retirement on female sexual function remains limited. In this study, we examined changes in female sexual function during the retirement transition.
Methods:
The population for this prospective follow-up study consisted of 110 women (mean age 63.1 y) from the Finnish Retirement and Aging study cohort. Data were collected annually before and after retirement. Sexual function was assessed with the Female Sexual Function Index questionnaire, which includes a total score and subdomain scores for desire, arousal, lubrication, orgasm, pain, and satisfaction.
Results:
The total Female Sexual Function Index score remained stable from preretirement to postretirement. The desire score improved from the preretirement level by 0.11 points (95% CI: 0.01-0.20, P=0.03), whereas the lubrication score changed by −0.29 points, although this change did not reach statistical significance (95% CI: −0.60 to 0.03, P=0.07). The scores for arousal, orgasm, pain, and satisfaction remained stable.
Conclusions:
During the retirement transition, sexual function remained mostly unchanged, but sexual desire improved. Future studies with longer follow-ups and larger sample sizes are warranted to investigate the evolution of female sexual function after retirement and identify the potential underlying factors of this phenomenon.